Retrosternal Ectopic Thyroid Mimicking Esophagus in Tc-99m Pertechnetate Thyroid Scan - Rajaraman, Vishnukumar (Indian J Nucl Med, 2019)
Abnormal Pertechnetate distribution can occur due to many reasons such as retrosternal extension of eutopic thyroid gland, ectopic functioning thyroid gland, physiological uptake in esophagus, teratoma having functioning thyroid tissue component, metastatic lymph nodes and sequestered thyroid nodule. We present a case of thyrotoxicosis with hyper functioning thyroid gland and two abnormal foci of uptake in the mediastinum in a linear fashion that mimcked esophageal activity. These foci persisted even after consuming water. SPECT localised these foci in retrosternal and likely to be ectopic functioning thyroid. Retrosternal ectopic thyroid tissue may not usually be detected on Tc-99m scan due to attenuation of low-energy gamma rays by sternal bone. However, hyperfunctioning tissue enabled visualization of the retrosternal ectopic thyroid.